DOI: 10.25148/etd.fi09082402
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship between Employee Virtuality and Technology Deviance as Mediated by Leadership and Employee Perceptions

Abstract: Recent studies found that organizations have been investing significant capital in developing teams and employees in geographic areas where labor and resources are considerably cheaper. Furthermore, organizations are moving core operational activities such as research and development and back-office processes to globally distributed teams.However, several factors that are inherent to these virtual teams can have a negative impact on employee perceptions and engagement; specifically, the physical and temporal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…For example, Salas (2009) revealed that employees who feel that their organisation is not supportive were more likely to engage in destructive behaviour. Furthermore, perceived organisational support was found to be negatively associated with supervisor-rated production deviance (Stamper and Masterson, 2002) and interpersonal deviance at work (Colbert et al, 2004).…”
Section: Organisational Justice and Workplace Deviant Behaviourmentioning
confidence: 96%
“…For example, Salas (2009) revealed that employees who feel that their organisation is not supportive were more likely to engage in destructive behaviour. Furthermore, perceived organisational support was found to be negatively associated with supervisor-rated production deviance (Stamper and Masterson, 2002) and interpersonal deviance at work (Colbert et al, 2004).…”
Section: Organisational Justice and Workplace Deviant Behaviourmentioning
confidence: 96%
“…According to Eder and Eisenberger (2006) perceived organisational support would increase employees' obligation to assist the organisation in achieving its goals hence, making them shun acts of deviance. Salas (2009) revealed that employees who feel that their organisation is not supportive were more likely to engage in destructive behaviour. Accordingly, organisational researchers argue that within the employer-employee relationship, not only are impersonal resources such as money, services, and information exchanged, but also socio-emotional resources such as approval, respect and support (Rhoades and Eisenberger, 2002).…”
Section: Organizational Support and Deviant Behaviourmentioning
confidence: 99%
“…Consistent with past studies, the results of present study indicated that subjective norm and social influence have both significantly correlated with AOC despite the strengths of correlations being considered moderate and low respectively. Prior studies have proved that employees received positive social pressure environment are more likely to be able to adapt and accept changes in workplace (Salas, 2009;Jimmieson et al, 2008;Schepers and Wetzels, 2007). Likewise, past researches have demonstrated that social influence had positively correlated employees' positive attitudes to accept organizational changes (Ferguson, 2007;Judge et al, 2006).…”
Section: Discussion On Research Findingsmentioning
confidence: 98%
“…In these studies, subjective norms were referred as peer, superior and family influence. When changes happened in workplace, the positive subjective norms were determined to be inclined with workers' receptive behavior (Salas, 2009). Similarly, evidence from many prior studies found that subjective norms have contributed and positively associated with various forms of workplace positive behavior (Eder and Eisenberger, 2008).…”
Section: H1 Locus Of Control Significantly Influences Aoc Among Management and Professionalmentioning
confidence: 91%